Intense and specialized dendritic localization of the fragile X mental retardation protein in binaural brainstem neurons: A comparative study in the alligator, chicken, gerbil, and human. Issue 9 (15th June 2014) - Wang, Yuan; Sakano, Hitomi; Beebe, Karisa; Brown, Maile R.; de Laat, Rian; Bothwell, Mark; Kulesza, Randy J.; Rubel, Edwin W
ABSTRACT Neuronal dendrites are structurally and functionally dynamic in response to changes in afferent activity. The fragile X mental retardation protein (FMRP) is an mRNA binding protein that regulates activity‐dependent protein synthesis and morphological dynamics of dendrites. Loss and abnormal expression of FMRP occur in fragile X syndrome (FXS) and some forms of autism spectrum disorders. To provide further understanding of how FMRP signaling regulates dendritic dynamics, we examined dendritic expression and localization of FMRP in the reptilian and avian nucleus laminaris (NL) and its mammalian analogue, the medial superior olive (MSO), in rodents and humans. NL/MSO neurons are specialized for temporal processing of low‐frequency sounds for binaural hearing, which is impaired in FXS. Protein BLAST analyses first demonstrate that the FMRP amino acid sequences in the alligator and chicken are highly similar to human FMRP with identical mRNA‐binding and phosphorylation sites, suggesting that FMRP functions similarly across vertebrates. Immunocytochemistry further reveals that NL/MSO neurons have very high levels of dendritic FMRP in low‐frequency hearing vertebrates including alligator, chicken, gerbil, and human. Remarkably, dendritic FMRP in NL/MSO neurons often accumulates at branch points and enlarged distal tips, loci known to be critical for branch‐specific dendritic arbor dynamics. These observations support an important role for FMRP in regulating dendritic properties of binaural neurons that are essential for low‐frequency sound localization and auditory scene segregation, and support the relevance of studying this regulation in nonhuman vertebrates that use low frequencies in order to further understand human auditory processing disorders. J. Comp. Neurol. 522:2107–2128, 2014. © 2013 Wiley Periodicals, Inc.